Crisis Diagnosis in Anti-Crisis Management Process in a Company - Ruta Meiste; Sandra Jakstiene (Institute of Economic Research (IER), 2015)
Crisis concept links up to its appearance area. Some different kinds and levels of crises have been found: we face with global, mainly nature cataclysm crises, state economic crises, corporate crises and individual or psychological crises. The research area of this paper is micro level, i.e. corporate crises or crisis in a company. However, it is emphasized that company is a sociotechnical system, performing in a complex environment, therefore crisis in a company is closely related to global and state crises, e.g. economic crises, which often cause the corporate crises, and to individual crises what can appear as crisis reason as well as crisis consequence. The relevance of the crisis situation diagnosis is confirmed by the diagnosis decisions designed and applied in the business practice, audit reports, bank assessment methods and company's own concernment. The aim of the research is to define crisis development stages and possible preventive means and to design the crisis diagnosis system in the anti-crisis management process in a company. The paper deals with four stages of crisis development: prodromal crisis (CP), acute crisis (CA), and chronic crisis (CC). Crisis resolution (CR) is the final goal of any crisis management. When crisis is overcome, its performance stabilizes and a company starts to grow. Therefore the main point in company's management process is to notice barrier when company's performance starts going down in order to foresee the result which can cause crisis situation in a company.
Keywords: M10; 330; crisis; diagnosis; anti-crisis management process